2007
DOI: 10.1051/0004-6361:20078641
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Hαsurges and ultraviolet jets above satellite sunspots

Abstract: Aims.To know more about the physical origin of surges and jets, we investigated seven successive surge events, which occurred above the satellite sunspots of active region NOAA 10720 on 2005 January 15. Methods. Using data from the Transition Region and Coronal Explorer (TRACE), Big Bear Solar Observatory (BBSO) and Solar and Heliospheric Observatory (SOHO), we present a detailed study of the surges and their relations with the associated small arch filament, UV jets, flares and photospheric longitudinal magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 33 publications
3
35
0
Order By: Relevance
“…However, the ejection directions of the two jets are not very consistent with each other. Similar phenomenon has also been reported by Chen et al (2008). In recent simulation of Pariat et al (2010), their results show that the drifting directions are different for recurrent jets, even if the underlying magnetic system and the driving motion remain constant.…”
Section: General Evolution Of the Jetsupporting
confidence: 80%
See 2 more Smart Citations
“…However, the ejection directions of the two jets are not very consistent with each other. Similar phenomenon has also been reported by Chen et al (2008). In recent simulation of Pariat et al (2010), their results show that the drifting directions are different for recurrent jets, even if the underlying magnetic system and the driving motion remain constant.…”
Section: General Evolution Of the Jetsupporting
confidence: 80%
“…Xu et al (1984) proposed a double-pole diffusion model to explain the rotating motion of a surge. However, in consideration of the close relationship between jets and photospheric magnetic flux activities, such as magnetic flux emergence, convergence, and cancelation etc (e.g., Roy 1973;Wang & Shi 1993;Shimojo et al 1998;Zhang et al 2000;Liu & Kurokawa 2004;Chen et al 2008), more authors incline to think that the spinning of jets results from the relaxation of magnetic twist, which occurs when twisted photospheric magnetic loop reconnects with ambient open fields (e.g., Shibata & Uchida 1986;Shibata et al 1994;Canfield et al 1996;Patsourakos et al 2008;Nisticò et al 2009;Kamio et al 2010;He et al 2010). Recently, three-dimensional simulations by Pariat et al (2009) show that high-level magnetic stress due to twisting motion can lead to an explosive release of energy via reconnection, which will produce massive, high-speed jets driven by nonlinear Alfvén wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially evident in active regions (ARs), where there are many observations of such cool ejections (e.g., Brooks et al 2007;Madjarska et al 2009;Wang et al 2014). Furthermore, surges are also associated with other phenomena such as light bridges (Asai et al 2001;Shimizu et al 2009; Robustini et al 2016) and explosive events (EEs), EUV or X-ray ejections (see, e.g., Schmahl 1981;Canfield et al 1996;Chen et al 2008;Madjarska et al 2009;Zhang & Ji 2014). It has also been suggested that surges can be related to Ellerman bombs (EBs; Watanabe et al 2011;Vissers et al 2013;Yang et al 2013); nevertheless, this relation does not seem to be common .…”
Section: Introductionmentioning
confidence: 99%
“…They may appear in the imaging observations as bright, dark, or dark-bright plasma structures as an emission or absorption features in various coronal/TR wavelengths (Chae et al 1999;Chen et al 2008;Liu & Kurokawa 2004;Ko et al 2005;Jiang et al 2007;Nishizuka et al 2008). The intra-relationship of the jets at different emissions has been explored in great details, e.g., in the Hα and soft X-ray (Rust et al 1977;Schmieder et al 1994;Canfield et al 1996), Hα and EUV (Schmahl 1981;Chae et al 1999;Jiang et al 2007;Chen et al 2008), and EUV and soft X-ray (Alexander & Fletcher 1999;Kim et al 2007;Chifor et al 2008a) emissions, which provides the clues on their exact driving mechanisms. The cool and hot component of the typical coronal jets have been physically explained by various magnetic reconnection based numerical models (Yokoyama & Shibata 1995.…”
Section: Introductionmentioning
confidence: 99%